Pemberdayaan Masyarakat dalam Pencegahan Demam Berdarah Dengue Melalui Budidaya Tanaman Zodia dan Pembuatan Cairan Anti Nyamuk Berbasis Serai - Asri Masitha Arsyati; Randi Irmayanto; Ade Nurhasanah; Apison Murib; Azra Ar Rasyid M.P; Deva Ramadhan; Eka Salma; Naufan Azkya; Salsabila Maulidina; Ulfia Rama Winando (Universitas Pahlawan Tuanku Tambusai, 2026)
Dengue Hemorrhagic Fever (DHF) remains a critical environmental health challenge in residential areas. West Java recorded Indonesia’s highest incidence from January to June 2025, reaching 17,281 cases. In Bogor City, 408 cases were reported (January–August 2025), a significant decrease from 2,817 cases during the same period in 2024. Cumulative 2024 data showed 3,094 cases and 16 deaths, following a fluctuating trend from 2021–2023 (526, 1,531, and 1,474 cases; 7, 9, and 9 deaths, respectively). This community service program in Villa Mutiara Bogor aimed to empower housewives through health education and natural lemongrass-based repellent production. Results showed a quantitative anomaly: the mean pre-test score (93.93) dropped to 40.71 in the post-test due to significant respondent attrition. Despite limited follow-up participation, the initiative successfully enhanced community awareness regarding environmental hygiene for sustainable DHF control.